Mental health care at the margins: bridging persistent access gaps in rural and underserved U. S. communities - Zerin, Farhana Faruque; Hegazy, Hadeer; Chanar, Suhail (International Journal Of Community Medicine And Public Health, 2026)
Mental health is a key component of public health, and access to behavioral health services remains uneven across the United States. Rural populations have higher rates of depression, anxiety, substance use disorders, and suicide, while they face limited access to mental health providers and services. These inequities are affected by structural, socioeconomic, and geographic factors, including economic instability, transportation barriers, and limited access to care, rather than differences in clinical need. Rural communities face ongoing difficulties due to provider shortages, inadequate mental health infrastructure, broadband inequities, and social stigma, which can hinder care-seeking behavior and exacerbate mental health outcomes. These barriers contribute to fragmented service delivery and diminished continuity of care for underserved populations.